Annotated Listing of New Books (Journal of Economic Literature, 2013)
Editor's Note Our policy is to annotate all English-language books on economics and related subjects that are sent to us. A very small number of foreign-language books are called to our attention and annotated by our consulting editors or others. Our staff does not monitor and order books published; therefore, if an annotation of a book does not appear six months after the publication date, please write to us or the publisher concerning the book. An Index of Authors of New Books appearing in the Annotated Listings will appear at the end of the General Index in the December issue.